Efektivitas Kegiatan Pendampingan Penderita Diabetes Melitus terhadap Peningkatan Kualitas Manajemen Diri - Rapitos Sidiq; Evi Maria Silaban; Marni Handayani; Evino Sugriarta (Poltekkes Kemenkes Padang, 2024)
Diabetes mellitus (DM) is a non-communicable disease which is currently causing complex problems both globally and nationally, because apart from the high morbidity and mortality rates. The main problem for DM sufferers is non-compliance in implementing a healthy lifestyle for DM sufferers, which has an impact on their quality of life due to complications. Efforts that can be made are to improve self-management with health education. The aim of this research is to determine the effectiveness of mentoring activities in improving the quality of self-management of DM sufferers. This research uses quantitative methods, with a quasi-experimental design, one group pre-test and post-test approach. The target activity is 64 people suffering from diabetes mellitus in Gunung Talang District, Solok Regency for more than 3 months, namely 27 May - 30 September 2022. The stages of data processing are editing, coding, transfer and tabulation. Data were analyzed bivariately using paired t-test with a confidence level of 95% (α=0.05). Data is presented in the form of tables and narratives. This research found that the average pre-test self-management score was = 45.6 while the post-test score = 50.89. The average pre-test blood sugar value = 226.09mg/dl and post-test value = 220.90 mg/dl. The conclusion is that mentoring activities are effective in changing the quality of self-management, but not blood sugar levels. It is recommended that this assistance activity be continued by the community health center so that the results can be maintained in the long term so that they can improve the quality of life of DM sufferers and have an impact on reducing their blood sugar.